The Influence of Brand Ambassador, Viral Marketing, and Brand Awareness on the Purchase Decision of Korean Skincare Products among University Students - Mawaddah, Siti; Siregar, Onan Marakali (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This research aims to explore how brand ambassadors, viral marketing, and brand recognition impact the buying choices of COSRX skincare items among college attendees in Medan. The study is motivated by the increasing craze for South Korean skincare in Indonesia, particularly among young people. COSRX, a leading K-beauty brand, has leveraged modern marketing strategies including celebrity endorsements and viral digital campaigns to strengthen its brand presence. A quantitative, associative research approach was employed, involving 100 student respondents in Medan who had purchased COSRX products. The study utilised a non-probability sampling method and gathered data through questionnaires, backed by a review of existing literature. Various analytical techniques, such as validity and reliability testing, tests of classical assumptions, multiple linear regression, and hypothesis testing (including t-tests, F-tests, and R²) were employed. The results suggest that brand ambassador, viral marketing, and brand awareness each have a positive and significant impact on consumers' purchasing choices. Significance was observed in the t-tests for brand ambassador (t = 5.462, p < 0.05), viral marketing (t = 4.710, p < 0.05), and brand awareness (t = 4.812, p < 0.05). Furthermore, the F-test indicated a substantial combined effect (F = 40.524, p < 0.05). The coefficient of determination (R²) stood at 55.6%, revealing that these three variables collectively explain more than half of the variation in purchase decisions, leaving 44.4% to be influenced by factors not considered in the study.